Boron doping of SWCNTs as a way to enhance the thermoelectric properties of melt‐mixed polypropylene/SWCNT composites - Krause, Beate; Bezugly, Viktor; Khavrus, Vyacheslav; Ye, Liu; Cuniberti, Gianaurelio (Giovanni); Poetschke, Petra (Energies, 2020)
Composites based on the matrix polymer polypropylene (PP) filled with single‐walled carbon nanotubes (SWCNTs) and boron‐doped SWCNTs (B‐SWCNTs) were prepared by melt‐mixing to analyze the influence of boron doping of SWCNTs on the thermoelectric properties of these nanocomposites. It was found that besides a significantly higher Seebeck coefficient of B‐SWCNT films and powder packages, the values for B‐SWCNT incorporated in PP were higher than those for SWCNTs. Due to the higher electrical conductivity and the higher Seebeck coefficients of B‐SWCNTs, the power factor (PF) and the figure of merit (ZT) were also higher for the PP/B‐SWCNT composites. The highest value achieved in this study was a Seebeck coefficient of 59.7 μV/K for PP with 0.5 wt% B‐SWCNT compared to 47.9 μV/K for SWCNTs at the same filling level. The highest PF was 0.78 μW/(m∙K2) for PP with 7.5 wt% B‐SWCNT. SWCNT macro‐ and microdispersions were found to be similar in both composite types, as was the very low electrical percolation threshold between 0.075 and 0.1 wt% SWCNT. At loadings between 0.5 and 2.0 wt%, B‐SWCNT‐based composites have one order of magnitude higher electrical conductivity than those based on SWCNT. The crystallization behavior of PP is more strongly influenced by B‐SWCNTs since their composites have higher crystallization temperatures than composites with SWCNTs at a comparable degree of crystallinity. Boron doping of SWCNTs is therefore a suitable way to improve the electrical and thermoelectric properties of composites.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Boron doping; Carbon nanotube; Polypropylene; Thermoelectric